1995
DOI: 10.1063/1.469621
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption spectra of linear carbon chains in neon matrices. II. C−2n, C2n, and C2nH

Abstract: Absorption spectra observed between 400 and 2500 nm in 5 K neon matrices have been assigned to electronic transitions of linear C−2n (n=2–10): 2Π←X 2Π, C2n (n=3–7): 3Σ−u←X 3Σ−g, and C2nH (n=3–8): 2Π←X 2Π chains. The species have been produced by mass selected deposition of cations or anions produced in a hot cathode discharge source (C2n, C−2n, C2nH) and by laser vaporization of graphite (C2n, C−2n). In addition to experimental and chemical evidence, the dependence of the absorption wavelength on the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 31 publications
11
121
0
Order By: Relevance
“…If one plots the wavelength of the origin band of the strong transition of HC 2n+1 H + in the visible range as a function of the number of carbon atoms, a linear dependence is observed, as has been noted for the à 2 ⌸ b ← X 2 ⌸ a transition and for other carbon chains. 31,32 The band at 547.2 nm of HC 11 H + departs considerably from this linear plot. This suggests that it is not the onset of the C transition.…”
Section: B Visible Spectral Rangementioning
confidence: 99%
“…If one plots the wavelength of the origin band of the strong transition of HC 2n+1 H + in the visible range as a function of the number of carbon atoms, a linear dependence is observed, as has been noted for the à 2 ⌸ b ← X 2 ⌸ a transition and for other carbon chains. 31,32 The band at 547.2 nm of HC 11 H + departs considerably from this linear plot. This suggests that it is not the onset of the C transition.…”
Section: B Visible Spectral Rangementioning
confidence: 99%
“…In Table II, the vertical excitation energies calculated in the present paper are compared with the experimental values. The papers of Maier and co-workers [12][13][14][15][16] provide low vertical energies for the lowest states. Generally, our MRCI vertical excitation energies agree relatively well with the experimental T 0 determinations of Refs.…”
Section: On the Electronic Excited States Of Cmentioning
confidence: 99%
“…For r-C 4 , Mühlhäuser et al 11 have located several singlet states in the 0 -5 eV internal energy range. Experimentally, numerous accurate data on these electronic states have been published by Maier and co-workers [12][13][14][15][16] and Jungen and Xu 17 using photoelectron spectroscopy and by the absorption spectra of C 4 in cold matrices. Xu et al 18 reported vertical excitation energies for l-C 4 from photoelectron spectroscopy and ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. 10 and 11), it became possible to record the electronic spectra of C 6 H, [12][13][14][15] among many other carbon chain radicals. In a combined microwave and optical study 16 the rotationally fully resolved origin band spectra of the B 2 -X 2 electronic system of C 6 H and C 6 D were analyzed, resulting in accurate spectroscopic parameters for both 2 states.…”
Section: Introductionmentioning
confidence: 99%